E-030 A rare case of subarachnoid hemorrhage caused by ruptured venous varix due to dural arteriovenous fistula at the foramen magnum. (23rd July 2017) - Lee, Y; Suh, S; Seo, S
Abstract : Introduction: Dural arteriovenous fistula (D-AVF) at the foramen magnum is an uncommon disease entity. It results in venous hypertension that is responsible for cervical myelopathy. On the other hand, it may rarely lead to an abrupt onset of a subarachnoid hemorrhage (SAH) when the venous varix is ruptured. The diagnosis of D-AVF as a cause of SAH may be difficult due to its low incidence, and the outcome could be fatal if the fistula is unrecognized. Herein, we report on a rare case of SAH caused by ruptured venous varix due to D-AVF at the foramen magnum. Material and Methods: A 48-year-old man experienced a sudden severe headache and neck pain while stretching his neck, and had another similar pain ten days later. After 3 more days with a far more aggravated symptom, he visited our ER. Brain CT showed SAH in the cistern magna. Cerebral angiography revealed a D-AVF at the foramen magnum supplied by hypoglossal branch of neuromeningeal trunk of ascending pharyngeal artery and drained into suboccipital vein and sigmoid sinus. There was a venous varix adjacent to the fistulous point, and it matched to the location of hematoma. Results: Superselective angiography via hypoglossal branch of neuromeningeal trunk of ascending pharyngeal artery was performed to delineate the anatomical locations of the fistulous point and the ruptured venous varix. A microcatheter was navigated to the point of fistula, and Onyx was slowly injected until the D-AVF and venous varix were completely obliterated. His symptom gradually disappeared within a few days. The follow-up angiography after 1 month also showed complete occlusion of the lesions. He discharged without any neurological deficits. Conclusion: D-AVFs at the foramen magnum, although extremely rare, should be considered as a possible cause of SAH. Detailed inspection of cerebral angiography is mandatory to prevent misdiagnosis. Onyx embolization can be a feasible treatment option to treat such D-AVF. When the D-AVF is fed by neuromeningeal trunk of APA, precise recognition of anatomical location of the lesion by superselective angiography and precise delivery of embolic materials to the fistulous point are required for successful and safe embolization, because there exist dangerous anastomoses between the APA and carotid and vertebral arteries and it carries a significant risk. Disclosures: Y. Lee: None. S. Suh: None. S. Seo: None.